Konsep Uang Perspektif Al-Ghazali - Mohammad Syarifuddin Amarullah; Yadi Janwari; Dedah Jubaedah (STAI Al-Mas'udiyah, 2025)
This research explores the concept of money according to Al Gazhali. Using a hermeneutic qualitative approach, this study interprets al Ghazālī's ideas on the function of النقد (money) as a medium of exchange (وسيلة التبادل), a store of value (حافظ للقيمة), and a measure of justice (ميزان العدل) that safeguards maqāṣid al sharīʿah (مقاصد الشريعة). The main findings show that al Ghazālī saw money دينار and درهم as the “spirit” of the market that must be sterile from manipulation, so violations such as hoarding (كنز) and reducing the metal's grade were considered threats to the public good (مصلحة). The discussion captures the relevance of these classical arguments to contemporary monetary issues, ranging from inflation to digital currencies. The conclusion asserts that al Ghazālī's normative humanism offers an ethical foundation for modern equitable monetary policy.